Lipid biochemical diversity and dynamics reveal phytoplankton nutrient-stress responses and carbon export mechanisms in mesoscale eddies in the North Pacific Subtropical Gyre - Shavonna M. Bent; Daniel Muratore; Kevin W. Becker; Benedetto Barone; Tara Clemente; Helen F. Fredricks; Henry C. Holm; David M. Karl; Benjamin A. S. Van Mooy (Frontiers in Marine Science, 2024)
Mesoscale eddies cause deviations from the background physical and biogeochemical states of the oligotrophic oceans, but how these perturbations manifest in microbial ecosystem functioning, such as community macromolecular composition or carbon export, remains poorly characterized. We present comparative lipidomes from communities entrained in two eddies of opposite polarities (cyclone–anticyclone) in the North Pacific Subtropical Gyre (NPSG). A previous work on this two-eddy system has shown differences in particulate inorganic carbon (PIC) and biogenic silica sinking fluxes between the two eddies despite comparable total organic carbon fluxes. We measured the striking differences between the lipidomes of suspended and sinking particles that indicate taxon-specific responses to mesoscale perturbations. Specifically, cyanobacteria did not appear to respond to increased concentrations of phosphorus in the subsurface of the cyclonic eddy, while eukaryotic microbes exhibit P-stress relief as reflected in their lipid signatures. Furthermore, we found that two classes of lipids drive differences between suspended and sinking material: sinking particles are comparatively enriched in phosphatidylcholine (PC, a membrane-associated lipid) and triacylglycerol (TAG, an energy storage lipid). We observed significantly greater export of TAGs from the cyclonic eddy as compared to the anticyclone and found that this flux is strongly correlated with the concentration of ballast minerals (PIC and biogenic silica). This increased export of TAGs from the cyclone, but not the anticyclone, suggests that cyclonic eddy perturbations may be a mechanism for the delivery of energy-rich organic material below the euphotic zone.